Uji Toksisitas Subkronik Ekstrak Etanol Biji Ketumbar (Coriandrum Sativum L.) Terhadap Fungsi Jantung Dan Paru-Paru Pada Tikus Jantan (Rattus Norvegicu.) - Jennie Try Varian Laoli; Nerly Juli Pranita Simanjuntak; Finna Piska (An-Najat, 2024)
Coriander seed plant (Coriandrum sativum.) Apiaceae family As an alternative medicine to reduce various risk factors for heart disease including LDL cholesterol levels and high blood pressure, characterization and preparation of ethanol extract of coriander seeds (EEBK) using the maceration method was the first step in this research, followed by with subchronic toxicity testing. Subchronic toxicity testing used male rats (Rattus Norvegicu.) each of which was divided into 5 groups, namely control CMC Na 0.5%, EEBK doses of 100, 200, 400 and 500 mg/kg bw. In the subchronic toxicity test, the parameters observed included toxic symptoms, changes in body weight, death, as well as microscopic and macroscopic examination of organs, including hematological examination. This observation lasted for 28 days. Subchronic test data were analyzed using the Statistical Product and Service Solution with two-way ANOVA, followed by the Tukey and Kruskal-Wallis post-hoc test. Findings from the subchronic toxicity study indicated that EEBK did not have a toxic effect, because there was no significant difference in changes relative organ weight, body weight, number of mouse deaths, toxic symptoms, organ macroscopic, and hematological values ​​were compared with the control group (P > 0.05).